The fun of it : random records of my own flying and of women in aviation - Earhart, Amelia, 1897-1937. (Chicago : Academy Press, 1977)
The first woman to solo across the Atlantic recalls her youth, early encounters with flying, career as a pilot, and feminine pioneers in aviation.
Reprint of the 1932 ed. published by Harcourt Brace, New York.
Keywords: Earhart, Amelia, -- 1897-1937.; Earhart, Amelia, -- 1897-1937.; Women in aeronautics; Air pilots; Women in aeronautics